Impact of Augmented Reality-Based Learning on Preparing Children for Creative Reading Skills in Childhood Education Stage - Rommel Mahmoud AlAli; Ali Ahmad Al-Barakat (Forum for Linguistic Studies, 2024)
This study investigated the impact of augmented reality (AR)-based learning on developing creative reading skills in early childhood education. Using validated instruments, including an AR-based learning guide, and a creative reading skills test, the study involved 254 primary school children from northern Jordan. The sample of the study was divided into an experimental group of 127 children who engaged with AR technology, and a control group of 127 children who received traditional teaching. Findings indicated that the experimental group scored significantly higher on the creative reading skills test than the control group. Statistical analysis using one-way ANOVA confirmed these differences as significant, underscoring the effectiveness of AR-based learning in improving creative reading skills. These results suggest that AR technology holds potential to develop learning outcomes in early childhood settings. Based on these findings, it is recommended to integrate AR technology into early childhood curricula to better support children’s creative reading abilities. As an engaging and interactive tool, AR can nurture creative thinking and cognitive skills that go beyond traditional teaching. Additionally, AR transforms learning into a stimulating, multidimensional experience that enhances children’s motivation to engage actively in the educational process. By creating virtual environments with interactive elements, AR aligns learning closely with real-world contexts, promoting innovative approaches to reading skill development. Further research should explore AR applications in other early childhood education areas, and expand AR-based educational tools, with an emphasis on adapting content to local cultural contexts to achieve effective, impactful results in children’s skills development.